1986
DOI: 10.1111/j.1471-4159.1986.tb13050.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Recognising the GABAA/Benzodiazepine Receptor Including Its Regulatory Sites

Abstract: Polyclonal antibodies have been raised against the GABA/benzodiazepine receptor purified to homogeneity from bovine cerebral cortex in deoxycholate and Triton X-100 media. Radioimmunoassay was applied to measure specific antibody production using the 125I-labelled gamma-aminobutyric acid (GABA)/benzodiazepine receptor as antigen. The antibodies specifically immunoprecipitated the binding sites for [3H]muscimol and for [3H]flunitrazepam from purified preparations. In addition, when a 3-[(3-cholamidopropyl)dimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…Lane G is taken from a separate immunoblot, hence two markers are shown. (Stephenson et al, 1986a was clearly revealed by the antibody reaction under comparable conditions ( Figure Ic, track F).…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…Lane G is taken from a separate immunoblot, hence two markers are shown. (Stephenson et al, 1986a was clearly revealed by the antibody reaction under comparable conditions ( Figure Ic, track F).…”
Section: Resultsmentioning
confidence: 64%
“…Thus, deglycosylation of the purified receptor was carried out using endoglycosidase F treatment and the products were detected by immunoblotting. After this treatment, it was found with an a subunit-specific polyclonal antibody (Stephenson et al, 1986a) that the a subunit disappeared and a major product about 8000 lower in Mr than the original a (Mr in the range 44-46 000, in three experiments) was detected in parallel with a minor product about 5000 lower in Mr than a (Mr in the range 48-49 000) (Figure 3a). When the final products from this treatment of the intact, denatured receptor were revealed by antibody 1A6, these, plus two additional products of Mr 57 000 (minor) and 55 000 derived from the ,3 subunit were found ( Figure 3B).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Flunitrazepam and Ro 7-1986/1 were gifts from Dr H. Mohler (Hoffman-La Roche, Basel, Switzerland) and chlorazepate was a gift from Boehringer lngelheim (Bracknell, England). All other materials were as noted elsewhere [3,17].…”
Section: Methodsmentioning
confidence: 99%
“…GABA and benzodiazepine receptor-binding assays, and SDS-PAGE under reducing conditions, were carried out as before [3]. Western blotting was performed according to [17,18].…”
Section: Methodsmentioning
confidence: 99%